Acute Toxoplasma infection in pregnant women worldwide: A systematic review and meta-analysis. - Ali Rostami; Seyed Mohammad Riahi; Despina G Contopoulos-Ioannidis; H Ray Gamble; Yadolah Fakhri; Malihe Nourollahpour Shiadeh; Masoud Foroutan; Hamed Behniafar; Ali Taghipour; Yvonne A Maldonado; Ali H Mokdad; Robin B Gasser (Public Library of Science (PLoS), 2019)
BACKGROUND:Acute Toxoplasma infection (ATI) during pregnancy, if left untreated, can cause severe adverse outcomes for the fetus and newborn. Here, we undertook a meta-analysis to estimate the worldwide prevalence of ATI in pregnant women. METHODS:We searched international databases for studies published between January 1988 and November 2018. We included population-based cross-sectional and prospective cohort studies that reported the prevalence of ATI in pregnant women. Data were synthesized using a random effect model to calculate the overall prevalence of ATI (with a 95% CI) in six WHO regions and globally. We also performed linear meta-regression analyses to investigate associations of maternal, socio-demographic, geographical and climate parameters with the prevalence of ATI. RESULTS:In total, 217 studies comprising 902,228 pregnant women across 74 countries were included in the meta-analysis. The overall prevalence of ATI in pregnant women globally was 1.1% (95% CI: 0.9-1.2%). In studies where more strict criteria for ATI were used, the overall prevalence was 0.6% (95% CI: 0.4-0.7%). The prevalence was highest in the Eastern Mediterranean region (2.5%; 95%CI: 1.7-3.4%) and lowest in the European region (0.5%; 95% CI: 0.4-0.7%). A significantly higher prevalence of ATI was found in countries with lower income levels (P = 0.027), lower human development indices (P = 0.04), higher temperatures (P = 0.02) and lower latitudes (P = 0.005) and longitudes (P = 0.02). CONCLUSIONS:The risk of acquiring ATI during gestation is clinically important and preventive measures to avoid exposure of pregnant women to Toxoplasma infection should be strictly applied.